PEMBIAYAAN PENDIDIKAN MADRASAH DAN PERANAN PEMERINTAH DAERAH DI ERA OTONOMI - Nunu Ahmad An-Nahidl (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2007)
by and comes from the community. For that reason the madrasah usually deals with problems with the community directly, and one of these problems is education costing. This survey wants to describe the type of education costing in madrasah and the role of kcal government. The survey found that the main obstacle in education costing is there was not enough support from community themselves in term of budgeting the local government only played an insignificant role in the building and development of madrasah.